Distributed optical fibre sensing technique in slope deformation monitoring - Ahmad, I.S. (Books and Journals Private Ltd., 2021)
Over the past decades, slope deformation monitoring has applied the use of traditional monitoring instruments, which among them is the widely used inclinometer. Such instrument possesses many disadvantages where it is prone to electromagnetic interference, requires numerous cable installations and limited sensing range. With the advancement of optical fibre sensing technology, researchers have started to look into its capability in monitoring slope deformation.The fully distributed optical fibre sensing (BOTDA) was employed in monitoring the horizontal deformation of a smart pipe installed in the medium-scaled laboratory slope model. The smart pipe is made up of a PVC pipe integrated with optical fibre cable and buried into the soil. The result obtained showed that the performance of the smart pipe was able to record the deformation when the slope was subjected to incremental surcharge loading. This study concluded that the smart pipe is able to replace the existing traditional inclinometer in improving geotechnical monitoring efficiency. Â© 2021, Books and Journals Private Ltd.. All rights reserved.